PENDAMPINGAN PEMANFAATAN APLIKASI KAHOOT DAN QUIZIZZ DALAM PEMBELAJARAN DI SMPN 37 PEKANBARU - Vita Nova Anwar; Sari Herlina; Dadang Juandi (Kanigara, 2023)
Kahoot and Quizizz are learning platforms that can be used to view student knowledge based on games. This application can be used as an ice breaker to raise student interest in learning. Quizizz and Kahoot applications can be used for all lessons. So that this mentoring activity aims to make teachers at SMPN 37 Pekanbaru able to take advantage of the Quizizz and Kahoot applications in learning so as to create a learning environment that attracts students' interest in learning and is able to make meaningful assessments for students. The implementation method begins with the delivery of material in a classical manner, followed by a question and answer session and mentoring in making quizzes through the kahoot and quizizz applications that are adapted to the material that the teacher is capable of. As a result of this service activity, teachers at SMPN 37 Pekanbaru as training participants have received assistance in using the Kahoot and Quizizz applications in learning. In this training the teachers have made quizzes and exercises using the Kahoot and Quizizz applications to be tested in their respective classes. In this training, teachers are very interested in preparing interactive technology-based learning tools.